National and Global Energy Governance: Issues, Linkages and Challenges in the Philippines - La Viña, Antonio Gabriel M (Archīum Ateneo, 2011)
This study examines the state of energy governance in the Philippines and assesses how domestic energy policies have shaped or been shaped by global energy institutions and issues. It analyzes the most pressing issues hounding the country’s energy sector, paying particular attention to the role of global and regional energy prices, the influence of bilateral and multilateral financial institutions, the impact of private sector investments, and climate change imperatives. Given the country’s lack of energy resources needed to fuel major economies today, the Philippines is unavoidably influenced by and participates actively in the dramatic and dynamic shifts in energy happening across the globe. Yet its greatest challenge is to secure its local energy needs amid an insecure and unpredictable global energy future and to balance this with equally important domestic concerns such as affordability of energy prices and environmental sustainability. For the Philippines, the priority is to build modern, competent, credible and accountable energy institutions that implement transparent and participatory governance processes in making energy decisions. Global energy governance and trends are important drivers that influence this critical institution‐building and modernizing process.